SARS and Kiribati: Eyes wide open - Zimmerman, Peta-Anne; Yeatman, Heather; Jones, Michael; Murdoch, Helen (International Journal of Infection Control, 2011)
A comprehensive infection prevention and control programme (IPCP) is designed to control and prevent the transmission of infectious diseases within the healthcare environment and the community. Understanding how an IPCP is introduced within a health system can inform actions to encourage their adoption in other locations. Data sources and analysis included: 1) Chronological and thematic analysis of IPCP documentation and assessments performed by local staff and external agencies/consultants, and 2) semi-structured interviews with local key informants and external agencies (using snow-ball sampling) with thematic analysis. Analysis was informed by Everett Rogers’ (2003) Diffusion of Innovations for Organisations framework. The two key activities of the organisational innovation process were identified. These were: initiation and implementation. The initiation activity included: 1) agenda-setting: preparations for severe acute respiratory syndrome (SARS) in 2003 stimulated the identification of organisational IPCP deficits, and 2) matching: deficits were identified and the decision to adopt an IPCP innovation package was made. Implementation included: a) redefining/restructuring: identification of the components of an IPCP and how they best fit within the local health structure, b) clarifying: integration of IPCP into the health services and defining an infection control role within the nursing division and, c) routinising: the IPCP became an ongoing element in health service delivery. The adoption of the IPCP followed the classic Diffusion of Innovations Process for Organisations. This process can serve as an IPCP adoption model in other low- and middle-income healthcare settings.